How do less‐expensive nitrogen alternatives affect legume sanctions on rhizobia? - Ryoko Oono; Katherine E. Muller; Randy Ho; Andres Jimenez Salinas; Robert Ford Denison (Ecology and Evolution, 2020)
Abstract The evolutionary stability of mutualistic interactions involving multiple partners requires “sanctioning”–the ability to influence the fitness of each partner based on its respective contribution. Sanctions must be sensitive to even small differences if even slightly less‐beneficial partners could gain a fitness advantage by diverting resources away from the mutualistic service toward their own reproductive fitness. Here, we test whether legume hosts sanction even mediocre N2‐fixing rhizobial strains by influencing either nodule growth (which limits rhizobial cell numbers) or carbon accumulation (polyhydroxybutryate or PHB) per rhizobial cell. We also test whether sanctions depend on the availability of less‐expensive nitrogen alternatives, either as nitrate or coinoculation with a more‐efficient isogenic strain. We found that nitrate eliminated differences in nodule size between the mediocre and more‐efficient strains, suggesting that host sanctions were compromised. However, nitrate additions also decreased PHB accumulation by the mediocre strain, which may eliminate any fitness advantages of diverting resources from N2 fixation. Coinoculation with a more‐efficient strain could also compromise host sanctions if reduction in fitness from smaller nodules does not offset the potential fitness gain from greater PHB accumulation that we observed in the mediocre strain. Hence, a host's ability to sanction mediocre strains depends not only on alternative sources of nitrogen but also the relative importance of different components of rhizobial fitness.